Kontribusi Perempuan Pengrajin Tenun Terhadap Ekonomi Keluarga Di Desa Bukit Batu - Hasbullah Hasbullah (Kafa`ah: Journal of Gender Studies, 2018)
This study aims to determine the woman contribution in the family economy. It is interesting to study because the Indonesian especially people in Riau province, the financial responsibility belong to men (husbands). Meanwhile women (wives) are often viewed as scaffolder of the family economy. This research is classified as qualitative method since it can captured and explained the phenomena. The results indicated that women weavers had a significant contribution in the household economy, particularly for those who had husband with decisive job and fixed income. Choosing this job as a source of economic income is a strategy to carry out their gender role in the domestic sector. They could earn money from the job without leaving the responsibility in caring their household